T cell assays for non-clinical immunogenicity risk assessment: best practices recommended by the European Immunogenicity Platform - Tourdot, Sophie; Karle, Anette Christine; Rosenbaum, Marc; Ackaert, Chloé; Le Vu, Pauline; Gutknecht, Michael; Ahmadi, Maryam; Turksma, Annelies W.; Hickling, Timothy P. (Frontiers in Immunology, 2026)
In vitro and in silico tools help drug developers reduce unwanted immunogenicity of biologics at the design stage. These include assays that examine different immune system processes leading to anti-drug antibody (ADA) or cytotoxic cellular response development, such as activation and peptide presentation by antigen-presenting cells, and CD4+ or CD8+ T cell activation, proliferation, and specificity. The CD4+ T cell response is critical for establishing persistent, class-switched and affinity-matured ADA that are more likely to have a clinical impact. Various formats of CD4+ T cell assays raise concerns about quality, variability, and validity across laboratories. Harmonization on some key aspects of these assays is achievable, although full standardization among industry and academic labs is unlikely. Thus, the European Immunogenicity Platform Non-Clinical Immunogenicity Risk Assessment working group (EIP-NCIRA) sought to establish good practices to maximize data confidence and ensure consistent data interpretation within each assay format. The recommendations presented regard key assay parameters that will better ensure consistency across the field including donor selection, cell and test article quality control, data analysis, as well as implementation of standard controls to further reduce analytical variability.